Anti-diarrheal, Analgesic and Anti-microbial activities of the plant Lalmesta (Hibiscus sabdariffa): A review - Sarkar, Md Raihan; Hossen, SM Moazzem; Howlader, Md Sariful Islam; Rahman, Md Ashfaqure; Dey, Avijit (International Journal of Pharmaceutical and Life Sciences, 2012)
The aim of this study was to phytochemically investigate the ethanolic extract of Hibiscus sabdariffa Linn. calyces and to evaluate the analgesic, anti-microbial and anti-diarrheal activities of this. The calyces of Hibiscus sabdariffa were separated from the other plant parts and sun dried and extracted using ethanol and phytochemically and pharmacologically evaluated.Different Phytochemical tests were performed for phytochemical screening and for determining the functional groups. Different methods like Disc diffusion method for antimicrobial activity determination, Castor oil induced diarrhea in mice method for the antidiarrheal study and Acetic acid induced writhing test for analgesic activity were employed. Phytochemical screening of the calyces of Hibiscus sabdariffa ensured the presence of alkaloid, flavonoids, saponins, tannins in the crude ethanolic extract. The peripheral analgesic activity was evaluated by acetic acid induced Writhing method. The extract produced 66.85% (p< 0.001) inhibition of writhing in mice at the dose of 500-mg/kg body weight, which is comparable to diclofenac sodium (78.45% (p<0.001) at the dose of 25mg/kg). The anti-diarrheal activity of the crude extract of Hibiscus sabdariffa was evaluated using the model of castor oil induced diarrhea in mice. The crude etanolic extract of Hibiscus sabdariffa (calyces) showed a marked antidiarrhoeal activity at dose of 500 mg/kg-body weight as compared to the standard antidiarrhoeal agent loperamide (dose:50mg/kg-body weight). Hibiscus sabdariffa caused an increase in latent period i.e. delayed the onset of diarrhoeal episode and decreased the frequency of defecation. Anti-microbial activity was tested using a number of micro-organisms. The peripheral analgesic activity of the ethanolic extract of the calyces of Hibiscus sabdariffa against acute inflammatory pain was significantly high as compared to potent inhibitory activity of Diclofenac (25mg/kg). Therefore, it is likely that the ethanolic extract at a dose of 400mg/kg might suppress the formation of these substances or antagonize the action of these substances and thus exerts its analgesic activity in acetic acid-induced writhing test. Anti-diarrheal activity was present in the ethanolic extract (500mg/kg) which indicate that the drug in decreased intestinal motility. This plant sample didnt show any antimicrobial activity. DOI: http://dx.doi.org/10.3329/ijpls.v1i3.12978 International Journal of Pharmaceutical and Life Sciences Vol.1(3) 2012